Characteristics of Stormwater Runoff in Different Land Use Areas - Sarukkalige, Priyantha Ranjan (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Research covered in this paper has outlined the basis for a detailed study into the specific effects of land use onstorm water runoff and drainage. It can be seen that the runoff is highly variable although still follows some basic trends with one of these being heavily based on land use. This study used different land use areas including residential, commercial, industrial and agricultural areas. Results show the temporal change of rainfall versus overland flow for each land use type. In addition the results concluded the rainfall – runoff relationship for each land use areas. It is obvious from the research carried out here that there are also a lot more factors that affect the runoff quantity and characteristics.